Making Hard Choices in Local Public Health Spending With a Cost-Benefit Analysis Approach - Robertson, Lee; Skelly, Chris; Phillips, David (Frontiers in Public Health, 2019)
Background In 2013, public health moved into Local Authorities, but initial optimism has been overtaken by serious ongoing financial constraints and an uncertain future. Hard choices have become an everyday reality across local authorities and for their public health teams. Assessing the return-on-investment of public health interventions and possessing economic evaluation skills have become more critical than ever before. Methods Using the New Economy cost-benefits-analysis model developed at the Greater Manchester Combined Authority, we undertook cost benefit analyses of some of our largest areas of commissioned spend in local public health practice to better understand both the public and fiscal returns of our interventions. Results The cost-benefit analyses indicated considerable variation in the public returns-on-investment for our commissioned spend with £1.37 to £6.81 returned for every £1 spent, and a fiscal return for every £1 invested of between £0.54 and £1.37. Additionally, the fiscal benefits of these public health interventions appear to primarily flow to the NHS, which accounts for about 94% of the fiscal return. Conclusion While cost-benefit modelling cannot provide a complete picture of ‘value’, it does provide decision-makers with a transparent metric that facilitates a whole-of system discussion on ‘intervention value’ and prevention at scale investments. This approach will support investment strategies when implementing Sustainability and Transformation Partnerships and Integrated Care Systems. However, these tools should be used to support robust decision-making processes, not as a replacement for or a short-circuiting of existing processes.